2018
DOI: 10.1021/acs.joc.8b01468
|View full text |Cite
|
Sign up to set email alerts
|

Benzylic Thio and Seleno Newman–Kwart Rearrangements

Abstract: The thermally induced O → S and O → Se migration reactions facilitate the rearrangement of O-benzyl thio- and selenocarbamates [BnOC(═X)NMe] (X = S or Se) into their corresponding S-benzyl thio- and Se-benzyl selenocarbamates [BnXC(═O)NMe] (X = S or Se). A series of substituted O-benzyl thio- and selenocarbamates were synthesized and rearranged in good yields of 33-88%. The reaction rates are higher for substrates with electron-donating groups in the 2 or 4 position of the aromatic ring, but the rearrangement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…For instance, a benzylic thio-and seleno-Newman-Kwart rearrangement was studied to provide mechanistic insights. [149] In this recent work, Pittelkow and co-workers have observed a fundamental change in the rearrangement mechanism when altering the phenyl group of the benzylic species. [150] The reaction was carried using both elements (S or Se), and the reaction kinetic was discussed based on the substrate scope.…”
Section: Minireviewmentioning
confidence: 97%
See 1 more Smart Citation
“…For instance, a benzylic thio-and seleno-Newman-Kwart rearrangement was studied to provide mechanistic insights. [149] In this recent work, Pittelkow and co-workers have observed a fundamental change in the rearrangement mechanism when altering the phenyl group of the benzylic species. [150] The reaction was carried using both elements (S or Se), and the reaction kinetic was discussed based on the substrate scope.…”
Section: Minireviewmentioning
confidence: 97%
“…Despite of the profound intellectual challenge to develop rearrangement reactions, currently, a great amount of information is presented in the literature. For instance, a benzylic thio‐ and seleno‐Newman‐Kwart rearrangement was studied to provide mechanistic insights [149] . In this recent work, Pittelkow and co‐workers have observed a fundamental change in the rearrangement mechanism when altering the phenyl group of the benzylic species [150] .…”
Section: Additional Information Through Organoselenium Compoundsmentioning
confidence: 99%
“…Although analogous O -alkyl thiocarbamate donors have been prepared and are stable under ambient conditions, we found that the O -alkyl thiocarbamate with the imine trigger isomerized to the S -alkyl pH-sensitive thiocarbamate ( S - pHTCM ) isomer both in the solution and also in the solid state (Figure S1). Thione–thiol isomerization is well known to occur in thiocarbamates via the Newman–Kwart rearrangement , but typically requires high temperatures or catalysts. , Similarly, benzylic Newman–Kwart rearrangements have recently been reported to occur at elevated temperatures . We hypothesize that the electron-donating imine substituent aids in the stabilization of the benzylic carbocation intermediate formed in the thiocarbamate rearrangement and, thus, may facilitate this isomerization under more mild conditions.…”
Section: Resultsmentioning
confidence: 87%
“…31,32 Similarly, benzylic Newman−Kwart rearrangements have recently been reported to occur at elevated temperatures. 33 We hypothesize that the electron-donating imine substituent aids in the stabilization of the benzylic carbocation intermediate formed in the thiocarbamate rearrangement and, thus, may facilitate this isomerization under more mild conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…Capped stick representation of the crystal structure of Tolnaftate 15, denoting π-π and CH-π interactions between adjacent naphthyl (in yellow) and phenyl (in blue) rings.Finally, Hirshfeld surface analysis (Figure S33-52)were performed on all 14 crystal structures, as well as selected O-thiocarbamate compounds namely ERIWEH,39 GIQDES,40 JELTUQ,41 JELVAY,41 VIVVUU,42 and ZAHHUO, 43 using CrystalExplorer.44 For most of the compounds analysed, the largest percentage contribution to the interatomic contacts of the Hirshfeld surfaces were mainly C-H/H-C (~ 20-30%), H-H/H-H (~ 15-65%) and H-S/S-H (10-20%) short-range contacts. Representative noteworthy close contacts are highlighted in Figure 7, specifically for 14, 15, and JELTUQ.…”
mentioning
confidence: 99%